The relationship between self-regulated learning and learning motivation with metacognitive skills in biology subject - Nanda Mulyadi Mustopa; Romy Faisal Mustofa; Dea Diella (University of Muhammadiyah Malang, 2020)
The latest learning in the 21st century requires learners to master various competencies to support their learning process and achieve the expected learning goals. This study aims to determine the relationship between self-regulated learning and learning motivation with metacognitive skills. The research was conducted in May 2020 at SMAN 1 of Tasikmalaya. The research used a quantitative approach to explore the correlation among variables observed involving a population of 177 students of class XI MIPA 1- XI MIPA 5 in academic year 2019/2020. The samples were 43 students selected using simple random sampling technique. Metacognitive Awareness Inventory (MAI) questionnaire adapted from Schraw & Dennison and Motivated Strategies for Learning Questionnaire (MSLQ) adapted from Pintrich & De Groot were used to collect the data. MAI is used to measure metacognitive skills, while MSLQ is used to measure self-regulated learning and learning motivation. MLSQ is a validated isntrumen, while MAI is tested for validity first and the results are valid. The analysis technique used was multiple linear regression tests. The results show that the correlation coefficient (R) was 0.747 and the coefficient of determination (R2) was 0.558. The contribution of self-regulated learning and learning motivation to metacognitive skills amounted to 55.8%.